2009
DOI: 10.1348/000712608x311731
|View full text |Cite
|
Sign up to set email alerts
|

Fetal testosterone and autistic traits

Abstract: Studies of amniotic testosterone in humans suggest that fetal testosterone (fT) is related to specific (but not all) sexually dimorphic aspects of cognition and behaviour. It has also been suggested that autism may be an extreme manifestation of some male-typical traits, both in terms of cognition and neuroanatomy. In this paper, we examine the possibility of a link between autistic traits and fT levels measured in amniotic fluid during routine amniocentesis. Two instruments measuring number of autistic traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
326
5
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(348 citation statements)
references
References 96 publications
(121 reference statements)
14
326
5
3
Order By: Relevance
“…Studies assessing these brain domains in people (both males and females) with ASD have found an extreme version of the male brain, where systemising is above average and empathy is reduced [55,56]. It has been hypothesised that high levels of fetal testosterone are responsible for the EMB [57]. This theory could therefore account for the cooccurrence of Gender Dysphoria and ASD in trans males (natal females), but not trans females [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing these brain domains in people (both males and females) with ASD have found an extreme version of the male brain, where systemising is above average and empathy is reduced [55,56]. It has been hypothesised that high levels of fetal testosterone are responsible for the EMB [57]. This theory could therefore account for the cooccurrence of Gender Dysphoria and ASD in trans males (natal females), but not trans females [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although no single biological basis for autism has been found, one specific finding has been demonstrated by positive correlations of foetal testosterone levels and autistic traits (Auyeung et al, 2009). The high-testosterone prenatal environment implicated in the etiology of ASDs supports a prominent theory of ASD (see 3.4).…”
Section: Causementioning
confidence: 99%
“…Despite these contradictory findings, the E-S theory is well supported by studies which suggest high levels of foetal testosterone are related to higher systemizing abilities in relation to empathising abilities and increased autistic traits (Auyeung et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The systemizing-empathizing hypothesis proposes that high levels of androgen exposure during prenatal development can cause an extreme masculinization of the brain, leading to a (pathological) bias toward systemizing and resulting in deficits in empathic processes, such as the theory of mind. Baron-Cohen and coworkers suggest that autism spectrum disorders-which are characterized by deficits in theory of mind-are caused by an "extreme male brain" but also present data that, even in typically developing humans, prenatal androgen exposure is predictive of autistic traits measured later in childhood (80).…”
Section: Becoming Humanmentioning
confidence: 96%